2014
DOI: 10.4103/0378-6323.140296
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an ablative and non-ablative laser procedure in the treatment of striae distensae

Abstract: We observed no satisfactory clinical improvement in striae distensae alba lesions although histopathological changes were seen. We suggest that variable square pulse Er: YAG and long pulse Nd: YAG lasers are not useful in the treatment of striae distensae alba.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…Many therapeutic modalities have been tried including topical retinoid, microdermabrasion, radiofrequency, photothermolysis, intense pulsed light, ablative and nonablative laser, and fractional lasers, but no consistently effective modality is available yet …”
Section: Introductionmentioning
confidence: 99%
“…Many therapeutic modalities have been tried including topical retinoid, microdermabrasion, radiofrequency, photothermolysis, intense pulsed light, ablative and nonablative laser, and fractional lasers, but no consistently effective modality is available yet …”
Section: Introductionmentioning
confidence: 99%
“…One was case report of two patients with axillary SD, compared 2940 nm Er:YAG AFL with a 585‐nm PDL, found 2940‐nm Er:YAG AFL had effect on improving the appearance of SD with 3‐5 treatment sessions, PDL treatment particularly was a good candidate for striae rubra, but lack of statistical evidence . Another split‐lesion study conducted by Gungor et al . compared the efficacy of 2940 nm variable square pulse (VSP) erbium: YAG laser and 1064 nm long pulse (LP) Nd:YAG laser on 20 female volunteers of SD, all subjects received three treatments monthly.…”
Section: Discussionmentioning
confidence: 99%
“…Following occlusion with a plastic film for 2 hours, the subjects received treatment with the 2940‐nm Er:YAG AFL 6 times at 4‐week intervals. According to our preliminary trial of two patients, we found after six times treatments the appearance of striae alba could achieve a significant improvement, combined with the studies in treatment of SD using 2940‐nm Er:YAG AFL devices and the patient's economic strength, the final choice was six times. The operator wore goggles, and the patient wore an eye mask.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although its molecular pathogenesis is not fully understood, evidence shows that stretch marks are caused by rapid stretching of the skin due to pregnancy, weight gain, rapid growth, also caused by diseases such as Cushing's syndrome and excessive use of steroids [1,4,5,6,7].…”
Section: Introductionmentioning
confidence: 99%